Vibrational courtship disruption of Nilaparvata lugens using artificial disruptive signals - Feng, Zelin; Wei, Qi; Ye, Zhongru; Yang, Baojun; Gao, Yufan; Lv, Jun; Dai, Yanyun; Bao, Jia; Yao, Qing (Frontiers in Plant Science, 2022)
The brown planthopper (BPH), Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) is a piercing-sucking pest that causes serious damage to rice plants by sucking the phloem sap from the plants and transmitting viruses. During courtship, the BPH vibrates its abdomen to produce signals that are transmitted to rice plants through its legs. Male BPHs search, locate, and mate with female BPHs after they exchange courtship signals with each other. Currently, spraying chemical pesticides is still the primary method for controlling BPH populations in paddy fields, although this approach has led to severe environmental pollution. A physical control method based on BPH courtship disruption to reduce the mating rate is a promising strategy for cutting environmental pollution. To acquire effective courtship disruptive signals, we developed a vibration signal recording, monitoring, and playback system for BPHs. Using this system, BPH courtship signals and male competition signals were collected and analyzed to obtain their frequency spectra. Results show that the mean main vibration frequency of female courtship signals is 234 Hz and the mean pulse rate is 23 Hz. The mean main vibration and pulse frequencies of the male courtship signals are 255 Hz and 82 Hz, respectively. Besides, the mean main vibration frequency of the male competition signal is 281 Hz. Seven different forms and frequencies of artificial signals were played back to male BPHs, then the courtship and behavioral responses of male BPHs were analyzed. Results indicate that a pure tone of 225 Hz prevents the males from recognizing female courtship signals. The male reply rate fell from 95.6% to 33.3% and the mean reply delay time increased from 5.3 s to 9.1 s. The reply rates of the other six artificial signals ranged from 42.9% to 83.7%, and the mean reply delays were between 5.0 s and 9.3 s. Therefore, the courtship behavior of BPHs can be disrupted by using specific artificial disruptive signals.